2017
DOI: 10.1080/13575279.2017.1299110
|View full text |Cite
|
Sign up to set email alerts
|

Spaces of connection and belonging: young people’s perspectives on the role of youth cafés in their lives

Abstract: A youth café is a relaxed, drug and alcohol free meeting space for young people. The youth café model has become a prominent form of policy provision for young people in Ireland over the past decade, with in excess of 160 youth cafes now in operation. While the youth cafe model is not unique to Ireland, there has been little published research internationally on the perspectives of young people regarding the role of youth cafes in their lives. Drawing on qualitative research with 102 young people in ten youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, our study found the more informal, relationship based youth work, such as youth clubs and project activities did not transfer to the online format so successfully. Previous research has shown that young people value the relationships and sense of belonging and safety that arises from “hanging out” in youth spaces, such as projects and youth cafes (Brady et al , 2018). While communication via digital technology is an intrinsic aspect of contemporary youth culture, the ways in which young people use these media in their everyday lives is complex and regulated by the social norms of peer groups (Buckingham, 2009, MacIsaac et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, our study found the more informal, relationship based youth work, such as youth clubs and project activities did not transfer to the online format so successfully. Previous research has shown that young people value the relationships and sense of belonging and safety that arises from “hanging out” in youth spaces, such as projects and youth cafes (Brady et al , 2018). While communication via digital technology is an intrinsic aspect of contemporary youth culture, the ways in which young people use these media in their everyday lives is complex and regulated by the social norms of peer groups (Buckingham, 2009, MacIsaac et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, research by Nolas (2014) on youth clubs shows that the young people were far less interested in the activities on offer and more interested in the opportunities provided by these activities to relate to each other and the youth workers. The author concluded that such "liminal spaces" need to be protected to ensure that young people can interact freely and "truly become themselves" (Nolas, 2014;Brady et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Shared spaces need to be developed and allow "co-clients" to attend in a shared space. Peers can be used as co-mentors, co-motivators and co-facilitators in group work and team activities (Brady et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Young people emphasised the importance of being connected to peers and having social networks. Relationships with peers encouraged young people to engage with services where they felt safe and not judged, and where they could receive and give support to one another (Brady et al, 2018). Young people valued being able to maintain their peer group and make new friendships within services, which helped build their confidence (Ritchie & Ord, 2017).…”
Section: The Importance Of Connecting With Peersmentioning
confidence: 99%
See 1 more Smart Citation